Revision de algunos criterios sobre la recomendacion de fertilizantes en frijol - Flor Montoya, Carlos A. (United Nations Development Programme, 1985)
The problem of fertilizer recommendations is discussed and each criterion to be considered is analyzed: amount of nutrients in the soil, crop requirements, fertilizer efficiency, and economic aspect of fertilization. A list of some var. tolerant to adverse soil conditions (low P, high Al) is presented as well as curves of nutrient uptake and of efficiency of fertilizer applications, and estimation of nutritional requirements. (CIAT)